A companion to moral anthropology - Fassin, Didier (Chichester, West Sussex: Wiley-Blackwell, 2012)
"A Companion to Moral Anthropology is the first collective consideration of the anthropological dimensions of morals, morality, and ethics. Original essays by international experts explore the various currents, approaches, and issues in this important new discipline, examining topics such as the ethnography of moralities, the study of moral subjectivities, and the exploration of moral economies. Represents the first collection to provide a broad picture of a new field of research, moral anthropology, that includes the ethnography of moralities, the study of moral subjectivities and the exploration of moral economies Investigates the central legacies of moral anthropology, the formation of moral facts and values, the context of local moralities, and the frontiers between moralities, politics, humanitarianism Features contributions from pioneers in the field of moral anthropology, as well as international experts in related fields such as moral philosophy, moral psychology, evolutionary biology and neuroethics "--
"A Companion to Moral Anthropology represents the first collective effort to bring together the various currents, approaches, and issues in this emerging field"--
pt. 1. Legacies -- pt. 2. Approaches -- pt. 3. Localities -- pt. 4. Worlds -- pt. 5. Politics -- pt. 6. Dialogues.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Anthropological ethics -- Handbooks, manuals, etc; SOCIAL SCIENCE / Anthropology / Cultural; Anthropological ethics; Electronic books; Handbooks and manuals; Electronic books